Análise na parametrização das indutâncias e resistência de um motor de indução trifásico utilizando o Método de Eelementos Finitos - Novacki, Débora Falcomer (2018)
This work presents an electromagnetic study in the parametrization of a three phase induction motor through the Finite Element Method (FEM). The research allows to know beforehand the characteristics of an engine without the necessity of the construction of a prototype. For this purpose, a systematic review of the Three Phase Induction Motor (MIT) was carried out, covering its electrical, constructive aspects, routine tests and fundamental equations that describe its operational characteristics. Similarly, the objective was to understand the finite element method applied to electric machines, as well as FEMM (Finite Element Method Magnetics), which uses this method to solve real physical problems. From a review of the literature and technical-scientific publications, the research concentrated on understanding the constructive parts of the motor and developing an algorithm that extracts the inductances and resistance of the rotor to a respective model of electromagnetic circuit of the machine through of data obtained by FEMM. The results obtained are interpolated and submitted to the least squares method, in order to find the best fit for the given set of data provided by the algorithm. In this context, the results of the implemented methodology are presented in this work with the objective of bringing a more feasible alternative in the estimation of the electromagnetic characteristics of the machine and the inductances and rotor resistance from the analysis of its internal geometry and the magnetic flux, without the need to build a machine or a prototype